PINK1‐induced phosphorylation of mitofusin 2 at serine 442 causes its proteasomal degradation and promotes cell proliferation in lung cancer and pulmonary arterial hypertension. Issue 8 (18th July 2021) - Dasgupta, Asish; Chen, Kuang‐Hueih; Lima, Patricia D. A.; Mewburn, Jeffrey; Wu, Danchen; Al‐Qazazi, Ruaa; Jones, Oliver; Tian, Lian; Potus, Francois; Bonnet, Sebastien; Archer, Stephen L.
Abstract: Impaired mitochondrial fusion, due in part to decreased mitofusin 2 (Mfn2) expression, contributes to unrestricted cell proliferation and apoptosis‐resistance in hyperproliferative diseases like pulmonary arterial hypertension (PAH) and non‐small cell lung cancer (NSCLC). We hypothesized that Mfn2 levels are reduced due to increased proteasomal degradation of Mfn2 triggered by its phosphorylation at serine 442 (S442) and investigated the potential kinase mediators. Mfn2 expression was decreased and Mfn2 S442 phosphorylation was increased in pulmonary artery smooth muscle cells from PAH patients and in NSCLC cells. Mfn2 phosphorylation was mediated by PINK1 and protein kinase A (PKA), although only PINK1 expression was increased in these diseases. We designed a S442 phosphorylation deficient Mfn2 construct (PD‐Mfn2) and a S442 constitutively phosphorylated Mfn2 construct (CP‐Mfn2). The effects of these modified Mfn2 constructs on Mfn2 expression and biological function were compared with those of the wildtype Mfn2 construct (WT‐Mfn2). WT‐Mfn2 increased Mfn2 expression and mitochondrial fusion in both PAH and NSCLC cells resulting in increased apoptosis and decreased cell proliferation. Compared to WT‐Mfn2, PD‐Mfn2 caused greater Mfn2 expression, suppression of proliferation, apoptosis induction, and cell cycle arrest. Conversely, CP‐Mfn2 caused only a small increase in Mfn2 expression and did not restore mitochondrial fusion, inhibit cell proliferation, or induce apoptosis. Silencing PINK1 or PKA, or proteasome blockade using MG132, increased Mfn2 expression, enhanced mitochondrial fusion and induced apoptosis. In a xenotransplantation NSCLC model, PD‐Mfn2 gene therapy caused greater tumor regression than did therapy with WT‐Mfn2. Mfn2 deficiency in PAH and NSCLC reflects proteasomal degradation triggered by Mfn2‐S442 phosphorylation by PINK1 and/or PKA. Inhibiting Mfn2 phosphorylation has potential therapeutic benefit in PAH and lung cancer.